Development of STEAM-PJBL Based IPAS LKPD to Improve Students’ Science Literacy - Yulianti, Dwi; Apri Wahyudi, Apri Wahyudi; Roy Kembar Habibi, Roy Kembar Habibi; Fitriadi, Fitriadi; Putra You Hendra, Putra You Hendra (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study aims to develop Student Worksheets (LKPD) for Natural and Social Sciences (IPAS) based on the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach and the Project Based Learning (PjBL) model to improve the science literacy of fourth-grade elementary school students. The research method used was Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). The test subjects consisted of 20 students and 3 educators at an elementary school in Bandar Lampung City. The results of validation by media, language, and material experts show that the developed LKPD is considered highly valid with an average Aiken’s V coefficient above 0.90. Practicality tests show that the LKPD is rated "Very Practical" by educators (86.1%) and students (86.6%), based on aspects of readability, ease of use, visual appeal, and meaningful content. Effectiveness testing was conducted through pretest and posttest science literacy tests, with results showing an increase in the average score from 53.00 to 81.00 and an n-Gain value of 0.65, which is classified as moderate. It can be concluded that STEAM-PjBL-based LKPD IPAS is suitable for use in learning because it meets the aspects of validity, practicality, and effectiveness. This product has the potential to be an innovative and contextual learning medium in supporting the strengthening of elementary school students’ science literacy.